2013
DOI: 10.1002/adma.201304238
|View full text |Cite
|
Sign up to set email alerts
|

Highly Efficient Non‐Precious Metal Electrocatalysts Prepared from One‐Pot Synthesized Zeolitic Imidazolate Frameworks

Abstract: A facile synthesis of non-PGM ORR electrocatalysts through thermolysis of one-pot synthesized ZIF is demonstrated. The electrocatalysts exhibit excellent activity, with a maximum volumetric current density of 88.1 A cm(-3) measured at 0.8 V in PEFC tests. This approach not only makes ZIFs-based electrocatalysts easy to scale up, but also paves the way for the tailored synthesis of electrocatalysts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
228
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 306 publications
(238 citation statements)
references
References 55 publications
8
228
0
1
Order By: Relevance
“…[7][8][9][10][11] Nonetheless, highly active FeNC catalysts usually suffer a quick current decay in acidic PEMFCs under a harsh operating condition, e.g., a constant voltage of 0.5 V with H 2 /O 2 . [12] It has been shown that MNC with highly graphitized carbon as catalyst supports, can exhibit decent fuel cell stabilities. For instance, Wu et al [13] obtained a stable fuel cell current for hundreds hours with the FeCo/N doped graphitized carbon at 0.4 V with H 2 /air feeds.…”
mentioning
confidence: 99%
“…[7][8][9][10][11] Nonetheless, highly active FeNC catalysts usually suffer a quick current decay in acidic PEMFCs under a harsh operating condition, e.g., a constant voltage of 0.5 V with H 2 /O 2 . [12] It has been shown that MNC with highly graphitized carbon as catalyst supports, can exhibit decent fuel cell stabilities. For instance, Wu et al [13] obtained a stable fuel cell current for hundreds hours with the FeCo/N doped graphitized carbon at 0.4 V with H 2 /air feeds.…”
mentioning
confidence: 99%
“…3,5 While the concept of ORR catalysis by materials or molecules comprising Fe or Co, nitrogen and carbon elements is known since 1964, 7 breakthroughs in the ORR activity and fuel cell performance that were necessary to seriously consider Fe(Co)-N-C catalysts as potential substitutes to platinum in the acidic environment of PEMFCs were reported only after 2008. 2,[8][9][10][11][12][13][14] While major advances in the ORR activity and power density of PEMFC comprising Fe(Co)-N-C based cathodes have been reported, the next grand scientific challenges are i) improved understanding of the structure of the active sites and ii) improved understanding of the degradation mechanisms. Depending on the latter, mitigation approaches might be very different: i) system-based solutions to avoid the transient high-potential polarization during start-up and shutdown, ii) catalyst-based approaches in order to avoid the formation of H 2 O 2 during ORR or to endow the catalysts with a higher graphitic character, iii) novel cathode designs in order to stabilize its electrical, hydrophilic and diffusion properties.…”
mentioning
confidence: 99%
“…[38,39,65] For precursor MOFs, You et al indicated that pyrolysis of ZIF-67 at 900 °C for 3 h under Ar generated carbonized ZIF-67 with a N content of only 1.1 wt%. [38] By contrast, carbonized ZIF-8 obtained by using the same pyrolysis conditions contained 8.6 wt% N, in which the percentage of pyrrolic and pyridinic N was 78.3%.…”
Section: Nitrogen Dopingmentioning
confidence: 99%
“…[58,60] For instance, in order to fabricate N-doped MOF-derived materials, zeolitic imiazolate frameworks (ZIFs), a subclass of MOFs composed of tetrahedrally coordinated transition metal ions (e.g., Zn, Fe, Co, Cu) and imidazolate (IM) ligands, are frequently utilized as the precursor and/or template because of their high N content and other preferred properties, such as large surface area and uniform particle size. [24,33,34,36,[38][39][40][41]44,53,[64][65][66][67][68][69] Recently, You et al reported the conversion of ZIF-67 (Co(MIM) 2 , MIM = methylimidazole) to Co-and N-doped carbon (CoNC) via direct pyrolysis, producing a N-doped material with high N content. [39] Similarly, Chen and co-workers studied porous carbon materials derived from a series of bimetallic ZIFs (BMZIFs), which are based on ZIF-8 and ZIF-67 with varied Zn/Co ratio.…”
Section: Nitrogen Dopingmentioning
confidence: 99%
See 1 more Smart Citation